(untitled) (Proceedings of the International Conference on Future of Education, 2023)
The availability of teaching materials that pay attention to local natural resources integrated into project-based learning is rarely found when chemistry learning occurs in the classroom. This research aims to develop learning modules and assess the impact of the module on chemical literacy and the entrepreneurial interest of students. This research adopts the 10-step development model by Borg and Gall 10 steps. The data collection instruments in this study are feasibility sheets, practicality sheets, student readability sheets, questions on chemical literacy skills, and entrepreneurial interest questionnaires. This study is a quasi-experimental research with a pretest-posttest one-group design. The total sample was 131 students of class XII high school science which was chosen using the cluster random sampling method. The Manova test was used to analyze differences in chemical literacy and entrepreneurial interest of learners in experimental and control classes. The results of this study show that: (1) The distribution of students’ chemical literacy skills in the very high category in the experimental class was 35.48% while the control class was 21.87%. The level of entrepreneurial interest of students in the category was very high in the experimental class at 67.74% and the control class at 21.87%, (2) the percentage of effective contribution of the module to chemical literacy and entrepreneurial interest is 47%, chemical literacy is 12.4%, entrepreneurial interest is 43.8%; (3) The practicality test of the module by five chemistry teachers showed a very practical category with a percentage of 84.5%. (4) The module readability test by students obtained a percentage of 91.26% in the very good category. Thus, modules that have been developed can increase students’ chemical literacy and entrepreneurial interest. Keywords: Entreprenurial interest, Chemical literacy, Module development, Project-Based Learning, Borg and Gall